Extensions of Certain Classical Summation Theorems for the Series F, F, and F with Applications in Ramanujan's Summations - Yong Sup Kim; Medhat A. Rakha; Arjun K. Rathie (International Journal of Mathematics and Mathematical Sciences)
Motivated by the extension of classical Gauss's summation theorem for the series . As applications, certain very interesting summations due to Ramanujan have been generalized. The results derived in this paper are simple, interesting, easily established, and may be useful.F